Functional and conformational transitions of mevalonate diphosphate decarboxylase from Bacopa monniera - Shakeel, Abbassi; Patel, Krunal; Khan, Bashir Mohammad; Bhosale, Siddharth H.; Gaikwad, Sushama M. (International Journal of Biological Macromolecules, 2016)
Functional and conformational transitions of mevalonate diphosphate decarboxylase (MDD), a key enzyme of mevalonate pathway in isoprenoid biosynthesis, from Bacopa monniera (BmMDD), cloned and overexpressed in Escherichia coli were studied under thermal, chemical and pH-mediated denaturation conditions using fluorescence and Circular dichroism spectroscopy. Native BmMDD is a helix dominant structure with 45% helix and 11% sheets and possesses seven tryptophan residues with two residues exposed on surface, three residues partially exposed and two situated in the interior of the protein. Thermal denaturation of BmMDD causes rapid structural transitions at and above 40 degrees C and transient exposure of hydrophobic residues at 50 degrees C, leading to aggregation of the protein. An acid induced molten globule like structure was observed at pH 4, exhibiting altered but compact secondary structure, distorted tertiary structure and exposed hydrophobic residues. The molten globule displayed different response at higher temperature and similar response to chemical denaturation as compared to the native protein. The surface tryptophans have predominantly positively charged amino acids around them, as indicated by higher K-SV for IC as compared to that for CsCl. The native enzyme displayed two different lifetimes, vi (1.203 +/- 0.036 ns) and tau 2 (3.473 +/- 0.12 ns) indicating two populations of tryptophan. (C) 2015 Elsevier B.V. All rights reserved.
Keywords: Aggregation; CD spectroscopy; Fluorescence quenching; Mevalonate diphosphate decarboxylase; Unfolding